Advantages and disadvantages of mobile applications for workplace health promotion: A scoping review. - Maren Junker; Markus Böhm; Helmut Krcmar (PLoS ONE)
Different interventions and methods are used for workplace health promotion (WHP) programmes, including mobile applications (apps), which have proven effective among different health outcomes if properly communicated and developed. However, knowledge is lacking on the potential advantages and disadvantages of using this technology for WHP compared with nontechnical WHP programmes to support employers in their decision making and effective development of such an intervention. To obtain an overview of factors that decision-makers should consider when deciding whether to implement an WHP app, we conducted a scoping review of studies that have evaluated WHP apps. Potential advantages and disadvantages of using mobile apps for WHP were summarised using a strengths, weaknesses, opportunities and threats (SWOT) analysis. Articles were included if they focussed on a WHP app, were published between 2007 and 2022 in German or English, and evaluated an app for the general employee population. Altogether, 38 studies were included in the review, demonstrating WHP apps' effectiveness among various use cases in terms of content, e.g., mindfulness or sleep, and target groups, e.g., office workers, nurses or pilots. Strengths were found in the context of adoption, convenience for users, the targeted employee group's reach and cost-effectiveness. However, the review also identified some disadvantages in apps, including technical difficulties and usage barriers, as well as challenges, e.g., privacy issues and maintenance costs. Generally, our review found that different factors need to be considered when deciding whether to implement a WHP app based on the individual company situation, e.g., shift work, content to be communicated, and expectations for health parameter screening, among many others. By summarising recent literature on WHP apps, this review uses scientific knowledge to give employers an overview of potential factors to consider in their decision making.